Ethical values ​​and their influence on the attitude of a professional in training at the UNJBG Academic Professional School of Human Medicine - Tacna, 2016 - Rodas Alejos, Pedro Casiano (2017)
To determine the influence of the ethical values on the attitude of a professional in formation in the School Academic Professional of Human Medicine of the UNJBG - Tacna; in the year 2015. A sample of 120 students from the 6 years of study was considered. The type of research was correlational observational; whose data collection was cross-sectional. lt was found that in this professional career there is an influence of the ethical values on the attitude of a professional in formation. IV year students are characterized by an adequate level of their ethical values; the students of the III year show the lowest values; the most prominent indicator was the "Psychological competence" and the one focused on improving, "Power and social order”. lt is concluded that there is a direct and significant relationship between the indicators of ethical values and indicators of the attitude of a professional in training at the Professional Academic School of Human Medicine of the UNJBG- Tacna.